(untitled) (Journal of Parents and Teachers, 2022)
Technology is here to stay in our schools, and having a strategy for its landing is key to safely face a real, effective and global digital transformation. Today more than ever we need to make sense of the possibilities of the digital world within the classroom to enrich the learning process of our students, providing them with the digital competence necessary for today’s world.